ERG rearrangement is specific to prostate cancer and does not occur in any other common tumor - Scheble, Veit J. (2010)
BACKGROUND: Identification of specific somatic gene alterations is crucial for the insight into the development, progression, and clinical behavior of individual cancer types. The recently discovered recurrent ERG rearrangement in prostate cancer (PCa) might represent a PCa specific alteration that has not been systematically assessed in tumors other than PCa. Aim of this study was to assess, whether the ERG rearrangement and the distinct deletion site between TMPRSS2 and ERG, both predominantly resulting in a TMPRSS2-ERG fusion, occurs in tumors other than PCa. DESIGN: We assessed 54 different tumor types (2942 samples in total) for their ERG rearrangement status by FISH. To calibrate, we analyzed 285 PCa samples for the ERG rearrangement frequency. Additionally, we interrogated a high-resolution SNP data set across 3131 cancer specimens (26 tumor types) for copy number alterations. RESULTS: None of the 54 different tumor types assessed by FISH harbored an ERG rearrangement, whereas the PCa samples revealed an ERG rearrangement in 31.2%–49.5%, depending on the cohort. Furthermore, within the 26 tumor types assessed for copy number alterations by SNP, the distinct deletion site between TMPRSS2 and ERG (21q22.2-3) was detectable exclusively in PCa. CONCLUSION: Although Ewing's sarcoma and AML have known rearrangements rarely involving ERG, we hypothesize that the ERG rearrangement as well as the distinct deletion site on 21q22.2-3 between TMPRSS2 and ERG, are PCa specific genomic alterations. These observations provide further insight into the oncogenesis of PCa and might be critical for the development of ERG rearrangement assessment as a clinical tool.